Technological Quality of Sugarcane Inoculated with Plant-Growth-Promoting Bacteria and Residual Effect of Phosphorus Rates - Fernandes, Guilherme Carlos [UNESP]; Rosa, Poliana Aparecida Leonel [UNESP]; Jalal, Arshad [UNESP]; Oliveira, Carlos Eduardo da Silva [UNESP]; Galindo, Fernando Shintate [UNESP]; Viana, Ronaldo da Silva [UNESP]; De Carvalho, Pedro Henrique Gomes [UNESP]; Silva, Edson Cabral da [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; Al-Askar, Abdulaziz A.; Hashem, Amr H.; AbdElgawad, Hamada; et al. (MDPI, 2023)
Phosphate fertilization in highly weathered soils has been a major challenge for sugarcane production. The objective of this work was to evaluate the foliar levels of phosphorus (P) and nitrogen (N) and the technological quality and productivity of second ratoon cane as a function of inoculation with plant-growth-promoting bacteria (PGPBs) together with the residual effect of phosphate fertilization. The experiment was carried out at the research and extension farm of Ilha Solteira, state of São Paulo, Brazil. The experiment was designed in a randomized block with three replications in a 5 × 8 factorial scheme. The treatments consisted of five residual doses of phosphorus (0, 45, 90, 135 and 180 kg ha−1 of P2O5, 46% P) applied at planting from the source of triple superphosphate and eight inoculations from three species of PGPB (Azospirillum brasilense, Bacillus subtilis and Pseudomonas fluorescens), applied in single or co-inoculation at the base of stems of sugarcane variety RB92579. Inoculation with PGPBs influenced leaf N concentration, while inoculations with Pseudomonas fluorescens and combinations of bacteria together with the highest doses exerted a positive effect on leaf P concentration. Co-inoculation with A. brasilense + Pseudomonas fluorescens associated with a residual dose of 135 kg ha−1 of P2O5 increased stem productivity by 42%. Thus, it was concluded that inoculations with Pseudomonas fluorescens and their combinations are beneficial for the sugarcane crop, reducing phosphate fertilization and increasing productivity.
Keywords: PGPBs; ratoon cane; residual phosphorus; Saccharumspp; sugarcane quality